Comparative proteomic analysis of the venom of the taipan snake, Oxyuranus scutellatus, from Papua New Guinea and Australia: Role of neurotoxic and procoagulant effects in venom toxicity - Herrera Vega, María (2012)
2082-04 Embargo por política editorial